Profile of The Incidence of Onychomycosis at RSUD Dr RM Djoelham Binjai for Period January 2017 – December 2021 - Hervina Hervina (Institute of Computer Science (IOCS), 2022)
Onychomycosis is a disease caused by a fungal infection of the base plate and nail matrix which can be caused by dermatophytes, candida and other fungi. This study is a retrospective descriptive study to describe the results of the onychomycosis patient identification examination. The population in this study were all patients with new onychomycosis visits recorded in the medical record data of RSUD Dr. RM Djoelham Binjai for the period January 2017 – December 2021 which matched the inclusion criteria. Data collection uses secondary data with total sampling technique. The results showed that the highest prevalence of onychomycosis patients aged 51-60 years was 12 patients (30.8%), the average female sex was 23 patients (58.9%) and work as a farmer was 16 patients (40.5%). It is recommended to patients to always maintain personal hygiene and from damp and closed conditions.